Deciphering organotropism reveals therapeutic targets in metastasis - Bautista, Jhommara; López-Cortés, Andrés (Frontiers in Cell and Developmental Biology, 2025)
Metastasis remains the principal cause of cancer-related mortality, yet its distribution across organs is far from random. Instead, tumor cells exhibit organotropism, a consistent preference for colonizing specific distant tissues, a phenomenon shaped by anatomical constraints, molecular crosstalk, and microenvironmental compatibility. Far beyond mere mechanical entrapment in vascular beds, metastatic dissemination reflects a coordinated interplay between tumor-intrinsic programs and organ-specific niches. Tumor-derived extracellular vesicles, cytokines, and matrix-remodeling enzymes actively precondition distant sites through pre-metastatic niche formation, creating permissive microenvironments primed for colonization. Simultaneously, tissue-specific immune landscapes, stromal compositions, and mechanical architectures determine the fate of disseminated tumor cells, whether they are eliminated, enter dormancy, or form macrometastases. Phenotypic plasticity, metabolic reprogramming, and immune evasion mechanisms equip subclones with the capacity to exploit these unique niches. Across cancer types, reproducible patterns of organotropic metastasis not only guide clinical surveillance and therapeutic stratification but also reveal vulnerabilities in the metastatic cascade. This review synthesizes emerging mechanistic insights across anatomical, immunological, and molecular domains to construct a comprehensive framework of organotropism, highlighting therapeutic opportunities to intercept metastasis at organ-specific checkpoints.